The Influence of Corporate Culture and Organizational Commitment on Financial Performance of Malaysian Organizations - Johari, Juliana (2002)
This study examined the influence of corporate culture and organizational commitment on financial performance in Malaysia. The study also examined the influence of corporate culture and organizational commitment on organizational characteristics (type, age and size). Deshpande and Farley's (1999) corporate cultural types and Meyer and Allen's (1990) organizational commitment types instruments were used in this study. As for financial performance, two types of performance measures were used: Profitability measures (Return on Assets, Return on Investment) and Liquidity measure (Current Ratio). A total of 101 public listed companies from various industries participated in the study. It was found that there were significant correlations between corporate culture and organizational commitment. Specifically, there was a relationship between consensual culture with all the three types of organizational commitment: affective, continuance and normative. Both entrepreneurial and competitive cultures were found to be correlated with affective and continuance competitive cultures were found to be correlated with affective and continuance commitments. Bureaucratic culture was not significantly correlated with any of the organizational commitment types. The analysis between corporate culture, organizational commitment and financial performance also showed that both corporate culture and organizational commitment had significant influence on the financial performance, especially for the profitability measures. Finally, it was found that corporate culture did not influence organizational characteristics. Nevertheless, organizational commitment was found to have significant influences on all the three types of organizational characteristics. From this research, we may conclude that an appropriate corporate culture in the right work environment could promote work and organizational commitment The right combination of both (corporate culture and organizational commitment types) can assist to enhance productivity and financial performance.